Miracle Prosperity and Business Practices of Africa’s Prosperity Teachers - Nel, Marius (Commercialisation of Religion in South Africa: A Pentecostal Approach, 2023)
The chapter investigates the family business model of some successful African prosperity teachers that represent some of Africa’s wealthiest families. Its purpose is to critique the authority, absolute leadership and autonomy of the leaders that, in some cases, leave no room for oversight boards and terminate in financial excesses and abuses of power. At the same time, they access financial resources by preaching a message that guarantees prosperity and health to adherents’ faith and financial contributions. By way of documentary analysis through a phenomenological approach utilising comparative literature analysis, the commercialisation of the gospel is described. The study finds that the prosperity message is popular in Africa and that some of the apostles or prophets preaching the message set themselves up as the “owner”-founder, president and chief executive officer of a ministry that they run like a business. Their wives, children and other relations assist them for their financial benefit. It changes the church into a family business operating without clear principles of accountability and transparency. Their behaviour is tainting the reputation of all other Pentecostals, leading in some cases to governmental interventions to impose fiscal regulations on the movement and requiring a suitable response from affected Pentecostal churches. The chapter closes with some proposals to address the issue.
paid